Effectiveness of Kinetic Games and Their Impact on Learning Some Basic Basketball Skills for Middle School Students - Ahmed Amer; Zahraa Al-juboori (College of Physical Education and Sport Sciences, 2024)
This study aims to identify the effectiveness of kinetic games and their impact on learning some basic basketball skills for middle school students. The hypotheses of this study suggest that there are statistically significant differences between the experimental and control groups in the post-tests, favoring the experimental group. The research problem was identified through monitoring and reviewing the teaching methods used in middle school physical education classes. It was found that most lessons lack variety in teaching methods and rely on traditional approaches, which do not cater to the individual differences among learners. Consequently, the learning outcomes among students vary, and mastery of skills is not achieved. This issue must be addressed, and solutions must be found. After thorough research and review, it was concluded that kinetic games are the best approach to solve this problem, as they are engaging and stimulating for learning skills. The experimental method was used for the experimental and control groups with pre-tests and post-tests, suitable for the sample and the research problem. The research population consisted of second-grade students at Al-Waseela Boys School, totaling 127 students divided into three sections (A, B, C). Section B was intentionally chosen (by lottery), comprising 42 students, from which 25 students were selected to form the experimental group, with 17 students excluded for statistical reasons. Section A represented the control group with 41 students, from which 25 were selected similarly. A pilot study sample consisted of 10 students from the research population but outside the main sample. After conducting the pilot study, the pre-tests were carried out, followed by the main experiment, which involved applying kinetic games to the experimental group for two months, with two educational units per week (Monday and Wednesday), totaling 16 units. After the main experiment, post-tests were analyzed statistically using SPSS software. The conclusion was that kinetic games play an effective role in learning some basic basketball skills for middle school students. Using kinetic games in skill learning is necessary due to their stimulating and engaging nature for learners